Conformations and dynamics of stars and dendrimers: the Gaussian Self-Consistent approach - Ganazzoli, F. (Condensed Matter Physics, 2002)
Some conformational and dynamical aspects of branched polymer are reviewed. We discuss the theoretical Gaussian Self-Consistent (GSC) approach proposed in our group and used to study the behaviour of regular star polymers and dendrimers in different solvent conditions. Within a single framework, we consider the unperturbed Θ state, as well as the goodsolvent state in comparison with other theoretical or simulation approaches, and with some experimental results. We also briefly report the further results obtained for amphiphilic copolymer stars in selective solvents so as to highlight the potentialities of the method, as well as its strengths and its shortcomings. Здійснено огляд деяких конформаційних та динамічних аспектів гілкових полімерів. Ми обговорюємо теоретичний гаусівський самоузгоджений підхід, запропонований у нашій групі, що використовується для вивчення поведінки регулярних зіркових полімерів та дендримерів в умовах різних розчинників. Ми розглядаємо в єдиних рамках як незбурений Θ -стан, так і стан доброго розчинення, в порівнянні з іншими теоретичними чи симуляційними підходами, а також з деякими експериментальними результатами. Ми коротко представляємо також подальші результати, отримані для амфіфільних кополімерних зірок у відбіркових розчинниках, з метою показати як можливості методу, так і його недоліки.